Augmentation of nutritional security through millets in Second Green Revolution - Gokulnath, G; Vallal Kannan, S; Rani, S; Ragavan, T; Sheeba, S; Prabakaran, K (Plant Science Today, 2025)
Millets are highly resilient crops that can thrive in diverse climatic conditions and marginal lands with minimal water and input requirements. As the world faces the challenges of climate change, population growth and food insecurity. Millets have emerged as promising crops for sustainable agriculture and a potential crop of the Second Green Revolution, which focuses on rainfed agriculture. These crops offer several advantages firstly, their ability to withstand climate fluctuations and suitability for rainfed conditions make them a climate-smart solution for crop production in the face of prolonged droughts and changing weather patterns. Secondly millets are nutritionally rich containing essential micronutrients and dietary fibres which can help address the prevalent issue of malnutrition in many parts of the world. However, the mainstream adoption of millets faces several challenges including limited research and development inadequate infrastructure and insufficient market integration. To unlock the full potential of millets in the Second Green Revolution a comprehensive approach is required encompassing research, policy support, market development and consumer awareness. By harnessing the unique features of millets, the agricultural sector can move towards a more sustainable, resilient and inclusive future contributing significantly to global food security and nutrition goals. These crops offer a promising solution to address the challenges posed by climate change and population growth while promoting sustainable and nutritious food production.